2016
DOI: 10.1002/jcp.25242
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of E2F in Liver Disease-Mediated Regulation in Biology and Cancer

Abstract: Uncoordinated cell growth is one of the fundamental concepts in carcinogenesis and occurs secondary to dysregulation of the cell cycle. The E2Fs are a large family of transcription factors and are key regulators of the cell cycle. The activation of E2Fs is intimately regulated by retinoblastoma 1 (RB1). The RB pathway has been implicated in almost every human malignancy. Recently there have been exciting developments in the E2F field using animal models to better understand the role of E2Fs in vivo. Genetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…However, our GSVA result and PPI network failed to discern a direct pretherapy overactivated hypoxia-related biological process in TACE nonresponders. Instead, we found that pathways related to an aberrant cell cycle and proliferation, including G2/M checkpoint, E2F, MYC, and mTORC1 were significantly enriched in TACE nonresponders [ 27 29 ]. However, some previous studies have suggested that there is a positive correlation between hypoxia and activated mTORC1 and E2F pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our GSVA result and PPI network failed to discern a direct pretherapy overactivated hypoxia-related biological process in TACE nonresponders. Instead, we found that pathways related to an aberrant cell cycle and proliferation, including G2/M checkpoint, E2F, MYC, and mTORC1 were significantly enriched in TACE nonresponders [ 27 29 ]. However, some previous studies have suggested that there is a positive correlation between hypoxia and activated mTORC1 and E2F pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…E2F is an important family of transcription factors that regulate the cell cycle, and both the E2F and MYC pathways can promote the progression of HCC. 40 , 41 Additionally, high NLRP6 expression has been associated with more abundant neutrophils, NK cells, DC cells, and other tumor‐antagonizing immune cells. These results showed that NLRP6 can be used as a prognostic biomarker for determining the prognosis and immune infiltration levels in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 is a proto-oncogenic gene that could induce both cell proliferation and tumor suppression by promoting apoptosis in the liver. 40 Rho GTPases are involved in regulating cell proliferation, differentiation, and apoptosis, and are closely related to the infiltration and distant metastasis of liver cancer. 41–46 KRAS participates in the RAS/RAF/MEK/ERK signaling pathway and is an important regulator of cell growth.…”
Section: Discussionmentioning
confidence: 99%